Investigations of novel heat pump systems for low carbon homes - Mempouo, B. (2011)
The European standard EN15450 states that the Coefficient of Performance (COP) target range for a Ground Source Heat Pump (GSHP) installation should lie within the range of 3.5 to 4.5; when used for heating a building, and a typical Air-Source Heat Pump (ASHP) has a COP of 2.0 to 3.0 at the beginning of the heating season and then decrease gradually as the ambient air becomes cooler, whereas a typical GSHP is in the range of 3.5 –4.0, also at the beginning of the heating season and then decrease gradually as heat is drawn from the ground. For these reasons, in the middle of winter, when the COP drop, the heat pumps can generally only be considered as a ‘pre-heating’ method for producing higher temperature heat such as domestic hot water. In addition soil presents certain difficulties, due to the high cost of drilling to position coils in the ground compare to air source, although frost formation on the evaporator in winter limits also limit the use of air source. Though technology advances or are needed to overcome those issues.